AKIBAT PERKAWINAN SIRI TERHADAP STATUS HUKUM ANAK (Studi Kasus Penetapan No 33/Pdt.P/2021/PN.Bla) - Anggun Kireina Pandiangan; Ratna D. E. Sirait; Kosman Samosir (Universitas Katolik Santo Thomas Medan, 2025)
The purpose of this study is to find out how the consequences of siril marriage on the legal status of children and to find out the basis for the judge's consideration to grant the application in the determination of Number 33/Pdt.P/2021/PN Bla. The research method used is a normative legal research method that uses secondary data as the main data source. Secondary data collection was carried out by studying documents on Establishment Number 33/Pdt.P/2021/PN Bla. The data obtained were processed and analyzed in a normative descriptive manner. Drawing conclusions is taken by a deductive method, meaning drawing conclusions from general to special. The results of the study are that according to Article 2 paragraph 1 of Law Number 1 of 1974, a marriage is considered valid if it is carried out in accordance with religious law, even though it is not officially recorded by the state (serial marriage). According to Article 6 Paragraph (1) of the KHI, every marriage must be held in front of and under the supervision of the Marriage Registrar. Paragraph (2) Marriages carried out outside the supervision of the Marriage Registrar do not have legal force. Even though it is fulfilled with conditions and harmony in marriage, if there is no registration in front of the Office of Religious Affairs (KUA), this marriage is said to be a serial marriage. As a result, children born out of wedlock are considered children out of wedlock and only have a civil relationship with their mother, not with their father. However, with the Constitutional Court decision No. 46/PUU-VIII/2010, children born out of wedlock have a civil relationship with their mother and their mother's family as well as with a man as their father which can be proven based on science and technology or other evidence according to the law and receive recognition through legal channels, and also includes a civil relationship with the father's family.